Analisis Kekuatan Rangka Mesin Pemecah Cangkang Kemiri Menggunakan Metode Elemen Hingga - Marianus Beatriks Djala Gili; Frederikus Mikael; Sebastianus Batik (Universitas Proklamasi 45, 2026)
The increasing demand for candlenut commodities has driven the need for appropriate mechanization to improve post-harvest processing efficiency, particularly in shell breaking, which is still predominantly performed manually. This condition requires machine innovation that not only increases production capacity but also ensures the structural reliability of the machine frame as the main load-bearing component. This study aims to analyze the structural strength of a candlenut shell crushing machine frame using theoretical calculations and Finite Element Analysis (FEA) through SolidWorks software. The frame is made of AISI 1020 steel with dimensions of 1000 × 785 × 459 mm and a 40 × 40 × 2 mm hollow profile. Loading conditions are defined based on five main load distribution areas. Simulation results show a maximum stress of 12.44 MPa, displacement of 0.024 mm, and a safety factor of 28.25, while theoretical calculations yield 28.05 MPa stress, 1.17 mm displacement, and a safety factor of 12.53. Significant discrepancies arise due to simplifications in analytical assumptions, whereas FEA provides a more realistic structural representation. Nevertheless, both methods confirm that the frame operates within safe limits, although the high safety factor indicates potential overdesign, suggesting the need for structural optimization to improve material efficiency.